2022
DOI: 10.3390/su142416490
|View full text |Cite
|
Sign up to set email alerts
|

The Greater the Contact, the Closer the Threat: The Influence of Contact with Nature on the Social Perception of Biodiversity Loss and the Effectiveness of Conservation Behaviours

Abstract: The public awareness of biodiversity loss is growing; however, citizens still engage in behaviours that are harmful to ecosystems, such as buying products shipped from across the world. Exploring the public’s understanding of biodiversity loss is fundamental to promoting behavioural change. To this purpose, we carried out two studies to test whether the psychological distance of biodiversity loss influences citizens’ shared ideas about biodiversity, depending on individuals’ contact with nature, and how this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Hence, a competing environmental problem was at the center of the network and was likely used as a substitute association in this case. Although climate change and biodiversity loss are two related but different issues ( Bosone and Bertoldo, 2022 ), the concept of climate change could be far more present in the public’s perception than biodiversity loss, with the latter potentially being perceived as a lesser global environmental problem than climate change. These related issues may be difficult to separate because biodiversity loss could be perceived as just one aspect of other environmental problems ( Kaltenborn et al, 2016 ; Legagneux et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, a competing environmental problem was at the center of the network and was likely used as a substitute association in this case. Although climate change and biodiversity loss are two related but different issues ( Bosone and Bertoldo, 2022 ), the concept of climate change could be far more present in the public’s perception than biodiversity loss, with the latter potentially being perceived as a lesser global environmental problem than climate change. These related issues may be difficult to separate because biodiversity loss could be perceived as just one aspect of other environmental problems ( Kaltenborn et al, 2016 ; Legagneux et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…When interpreting the present results, additional research on social representations may be required to investigate the role of humans in relation to their contact with nature. According to Bosone and Bertoldo (2022) , individuals who frequently engage with nature had a greater awareness of the threat to biodiversity posed by human activities. Furthermore, such individuals tend to perceive this threat as being more imminent when compared to those who have limited exposure to nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies exploring the public perception of air pollution focus on individuals’ subjective evaluations of the pollution levels where they live, and the risks that this can have with regards to their health ( Bickerstaff and Walker, 1999 , 2001 ; Bush et al, 2001a , b ; Howel et al, 2003 ). Although there are no studies specifically concerning individuals’ perception of the environmental risks of air pollution, it has been demonstrated that individuals generally tend to represent environmental risks such as climate change ( Brulle et al, 2012 ; Spence et al, 2012 ; Kohut and Pew Research Center, 2013 ; Leiserowitz et al, 2013 ; Stoknes, 2014 ) and biodiversity loss ( Bosone and Bertoldo, 2022 ) as distant threats. These phenomena are indeed perceived as psychologically distant ( Trope and Liberman, 2010 ; Spence et al, 2012 ), something happening in a distant future (a sub-dimension defined as temporal distance), to other people (social distance), in faraway geographical areas (geographical distance) and with a relative degree of uncertainty (uncertainty).…”
Section: Introductionmentioning
confidence: 99%